The importance of personal financial planing among employee. Case study: Perbadanan Kemajuan Negeri Melaka / Nurul Atiqah Zulkifle - Zulkifle, Nurul Atiqah (2011)
The study was conducted to determine the relationship between employees’ level of knowledge and awareness regarding the personal financial planning with their attitudes towards personal financial planning. The dependent variable in this study is employees’ attitudes towards personal financial planning and the independent variables are employees’ level of knowledge and awareness. The study was conducted from 22nd November 2010 until 11th April 2011 which covers 50 respondents from Perbadanan Kemajuan Negeri Melaka. 50 questionnaires were distributes to respondents who willing to answer the question and the entire questionnaire managed to be collected. SPSS 18 were used to analyze data collected and multiple regression technique was used to test the hypothesis. From the findings, there is significance relationship between employees’ level of awareness with their attitudes towards personal financial planning whereas there is no significance relationship between employees’ level of knowledge with their attitudes towards personal financial planning.